ANALISIS PENGUKURAN KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD (Studi pada PT XL Axiata Tbk – Jakarta) - Darmasto, Bonifatius; Kamaliah, Kamaliah; Agusti, Restu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2014)
This study aims to analyze performance PT XL Axiata TbkJakarta using Balanced Scorecard method. Data used is primary dataobtained via questionnaires and interview, and secondary data frompublished source, literature and financial statement or otherpublications relating to the company. Balanced Scorecard methodused to assess the performance of company, because this method notonly measure financial perspective, but also non financial perspective;customer perspective, process business internal perspective andlearning and growth perspective. As the result can be concluded that(1) the performance evaluation with Balance Scorecard method can beimplement on PT XL Axiata Tbk Jakarta. All indicators show goodconditions. (2) Need support all departments in company to improvethe quality of measurement results. (3) PT Xl Axiata Tbk Jakarta hasshowed its capability. This is proven by company can compete withthe other for second position in national mobile business.